Introduction and Purpose of the Issue. Issue 3 (August 2019) - Baker, Rose M.
The Problem: This issue of Advances in Developing Human Resources addresses the establishment of a research agenda for theories and constructs selected from established theories from other fields of study, which are related to elements of the study of human resource development (HRD). Several of the theories or constructs were selected for inclusion in this issue based on prior publications in Academy of Human Resource Development (AHRD)–sponsored journals in which authors suggested the use of the theory to advance the theory, research, and practice in HRD. Other theories and constructs were inspired to be included by calls for interdisciplinary and multi-paradigmatic empirical research from journals within the economics, management, organizational psychology, and sociology fields of study. The Solution: Integrated, systematic, or theoretical literature reviews were conducted for each of the selected theories or constructs. Models, research propositions, and research agendas were developed to provide recommendations for the development of research designs and protocols. The goal of the implementation of the research agendas is to advance the theoretical foundations of HRD. The Stakeholders: This issue is expected to benefit HRD researchers and HRD practitioners by providing suggestions for empirical research studies to be conducted to explore HRD-related concepts using the theories selected and to establish interdisciplinary and multi-paradigmatic research opportunities.